Malnoms graciosos de criminals desgraciats entre les sentències de contenció del canceller de Catalunya (segles XVI-XVII). - CAPDEFERRO, JOSEP (Scripta, 2023)
Unexpectedly, in a prestigious collection of sentences issued by the chancellors of early modern Catalonia, several malefactors who sought the protection of ecclesiastical asylum were designated by their respective nicknames, in addition to their first and last names and, often, other identifying circumstances. Thus, the deep rootedness of this popular mechanism to designate people (of a certain social extraction?) is confirmed. Most of the seventy-five nicknames found are quite funny and provide information on the origin, characterization or complementary elements of the offenders. Only some are totally enigmatic to contemporary eyes (which is quite understandable, they often had an arbitrary or random component).